2018
DOI: 10.1021/acs.bioconjchem.7b00665
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Evaluation of Bioorthogonal Decaging with trans-Cyclooctene: The Effect of Fluorine Substituents on Aryl Azide Reactivity and Decaging from the 1,2,3-Triazoline

Abstract: Bioorthogonal prodrug activation/decaging strategies need to be selective, rapid and release the drug from the masking group upon activation. The rates of the 1,3-dipolar cycloaddition between a trans-cyclooctene (TCO) and a series of fluorine-substituted azido-PABC self-immolative spacers caging two model drugs, and subsequent release from the 1,2,3-triazoline are reported. As the number of fluorine substituents on the PABC linker increases from one to four, the rate of cycloaddition increases by almost one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…Next we investigated the dissolution of hydrogel 1 using TCO as the bioorthogonal trigger (Scheme ). The same mechanism as for prodrug activation was proposed for hydrogel dissolution. In the first step, 1,3‐dipolar cycloaddition between TCO and azide 1 is expected to result in the formation of 1,2,3‐triazoline 6 , which is relatively unstable under aqueous conditions and converted to the imine 7 via extrusion of diatomic nitrogen (expected to result in visual bubbles within the gel).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next we investigated the dissolution of hydrogel 1 using TCO as the bioorthogonal trigger (Scheme ). The same mechanism as for prodrug activation was proposed for hydrogel dissolution. In the first step, 1,3‐dipolar cycloaddition between TCO and azide 1 is expected to result in the formation of 1,2,3‐triazoline 6 , which is relatively unstable under aqueous conditions and converted to the imine 7 via extrusion of diatomic nitrogen (expected to result in visual bubbles within the gel).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to estimate the rate of the 1,3‐dipolar cycloaddition for hydrogel 1 , we monitored the reaction of azido‐dipeptide 1 and TCO in solution phase (MeCN:PBS; 1:1). Using HPLC (Figure S9 and S10), the disappearance of 1 ( R T =7.9 min) was measured under pseudo first‐order conditions (at 254 nm), and the second‐order rate constant was determined as 0.018 m −1 s −1 , a rate comparable to our previously reported bioorthogonal prodrug activation . In the absence of HPLC data on the gel‐sol transition itself, we performed a time‐dependent analysis of the 1,3‐dipolar cycloaddition using IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cycloaddition step occurs at a rate of 0.137 m −1 s −1 (mouse serum/PBS (1:1), T =37 °C); however, degradation of the triazoline and imine hydrolysis might both be rate limiting. In an effort to accelerate the reaction, fluorine substituents were introduced onto the p ‐azidobenzyl ring . A structure–reactivity analysis revealed that the introduction of fluorine substituents increased the rate of the cycloaddition step, but decelerated the 1,6‐elimination step from PABC.…”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
“…In an effort to accelerate the reaction, fluorine substituents were introduced onto the p-azidobenzyl ring. [75] A Scheme9.Reactionmechanism between vinyl ether derivatives and tetrazines. Following cycloaddition and the expulsion of nitrogen gas, aromatization of the pyridazines tructure affords efficient release of the leavinggroup.…”
Section: Release Triggered By Strained Alkenes and Alkynesmentioning
confidence: 99%